2016 White Paper on recent issues in bioanalysis: focus on biomarker assay validation (BAV): (Part 2 – Hybrid LBA/LCMS and input from regulatory agencies). (December 2016) - Song, An; Lee, Anita; Garofolo, Fabio; Kaur, Surinder; Duggan, Jeff; Evans, Christopher; Palandra, Joe; Donato, Lorella Di; Xu, Keyang; Bauer, Ronald; Bustard, Mark; Chen, Linzhi; et al.
The 2016 10th Workshop on Recent Issues in Bioanalysis (10 th WRIB) took place in Orlando, Florida with participation of close to 700 professionals from pharmaceutical/biopharmaceutical companies, biotechnology companies, contract research organizations, and regulatory agencies worldwide. WRIB was once again a 5-day, weeklong event – A Full Immersion Week of Bioanalysis including Biomarkers and Immunogenicity. As usual, it is specifically designed to facilitate sharing, reviewing, discussing and agreeing on approaches to address the most current issues of interest including both small and large molecules involving LCMS, hybrid LBA/LCMS, and LBA approaches, with the focus on biomarkers and immunogenicity. This 2016 White Paper encompasses recommendations emerging from the extensive discussions held during the workshop, and is aimed to provide the bioanalytical community with key information and practical solutions on topics and issues addressed, in an effort to enable advances in scientific excellence, improved quality and better regulatory compliance. This White Paper is published in 3 parts due to length. This part (Part 2) discusses the recommendations for Hybrid LBA/LCMS and regulatory inputs from major global health authorities. Parts 1 (small molecule bioanalysis using LCMS) and Part 3 (large molecule bioanalysis using LBA, biomarkers and immunogenicity) have been published in the Bioanalysis journal, issues 22 and 23, respectively.